Experiments and Computational Research of Biomass Pyrolysis in a Cylindrical Reactor - A. V. Mitrofanov; V. E. Mizonov; S. V. Vasilevich; M. V. Malko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article features an experimental study of thermally thin biomass samples (beech wood particles 17×8×6 mm) pyrolysis in a laboratory scale batch reactor. The reactor was a cylindrical steel body with internal diameter of 200 mm and height of 500 mm. The temperature of a lateral surface of the cylinder during the experiment was being kept constant (550 °C) due to electrical heating. The initial loading of the apparatus was about 4 kg with moisture content of about 14 % by weight. During the experiment, the temperature values of the material being pyrolyzed were recorded at two points of the radial coordinate, viz. at the wall of the apparatus and on its axis. A one-dimensional numerical model of the nonstationary process of biomass conversion (heat and mass transfer in combination with the Avrami – Erofeev reaction model) has been proposed and verified. The reactor is represented as a set of a countable number of cylindrical layers, considered as cells (representative meso-volumes) with an ideal mixing of the properties inside. The cylindrical surfaces that form cells are considered to be isothermal. The size of the cells is chosen to be sufficiently large in comparison with the individual particles of the layer, which makes it possible to consider the temperature field inside the cell volume as monotonic. The evolution of the temperature distribution over the radius of a cylindrical reactor is determined on the basis of a difference approximation of the process of non-stationary thermal conductivity. The calculated forecasts and experimental data showed a good agreement, which indicates the adequacy of the developed mathematical model of pyrolysis and makes it possible to recommend it for engineering calculations of biomass pyrolysis. This model can also be useful in improving the understanding of the basic physical and chemical processes occurring in the conditions of biomass pyrolysis.